(3GdGYdGe hGdGYdGe GdCefj eY OQGSGJ JWHjbjI ebGQfI ddOhd GdYQHjI (B/s - (3GdHGR,Ydj s ((3eUQ (B:s (3ecJHI GdGTYGY GdafjI ,s, 2001)
(3jOhQ ehVhY gPG GdcJGH Mhd eaghe GdGYdGe hhXGFag (B-(3eaghe GdGJUGd (B-(3GdOYGjI (B-(3GdYdGbGJ GdYGeI (B-(3GdGYdGf (B-(3GdhSGFd (B-(3GdJdaRjhf (B-(3GdGPGYI (B-(3GdSjfeG (B-(3GdSQM (B-(3GdUMGaI (B-(3hSGFd GdGYdGe h GdYfa h GdLQjeI (B-(3GdTQWI GdJbdjOjI h GdTQWI GdeLJeYjI (B-(3GdQCj GdYGe (B-(3hSGFd JchjfI h hSGFd bjGSg h CNjQG JCKjQ GdGYdGe aj GdTQWI h JCKQg HgG s
Keywords: (3GdGYdGe s; (3GdGYdGe GdCefjs; (3GdOhd GdYQHjIs